Control and Physiological Determinants of Sympathetically Mediated Brown Adipose Tissue Thermogenesis - Richard, Denis; Monge Roffarello, Boris; Chechi, Kanta; Labbé, Sébastien M.; Turcotte, Éric (Frontiers in Endocrinology, 2012)
Brown adipose tissue (BAT) represents a remarkable heat-producing tissue. The thermogenic potential of BAT is conferred by uncoupling protein 1, a protein found uniquely in the brown adipocytes. The physiological control of BAT activity and capacity is ensured by the sympathetic nervous system (SNS), which densely innervates brown fat depots. SNS-mediated BAT thermogenesis is essentially governed by hypothalamic and brainstem neurons. BAT is not only controlled by the brain thermoregulatory circuits but also by brain energy balance pathways including the very significant brain melanocortin system, which speaks in favor of the genuine involvement of SNS-mediated BAT thermogenesis in energy homeostasis. The use of positron emission tomography/computed tomography (PET/CT) scanning has further revealed the presence of well-defined BAT depots in the cervical, clavicular, and paraspinal areas in adult humans. The prevalence of these depots was reported to be higher in subjects exposed to low temperature and was also higher in women than men. Moreover, the prevalence of BAT was shown to decrease with age and body fat mass, which suggests that BAT could not only be involved in cold-induced non shivering thermogenesis but also in the energy balance regulation and obesity in humans. This short review summarizes recent progress made in our understanding of the control of SNS-mediated BAT thermogenesis and of the determinants of BAT prevalence or detection in humans.